2017
DOI: 10.1186/s12883-017-0908-0
|View full text |Cite
|
Sign up to set email alerts
|

Nasal administration of the neuroprotective candidate NeuroEPO to healthy volunteers: a randomized, parallel, open-label safety study

Abstract: BackgroundDelivery of therapeutic agents as erythropoietin (EPO) into Central Nervous System through intranasal route could benefit patients with neurological disorders. A new nasal formulation containing a non-hematopoietic recombinant EPO (NeuroEPO) has shown neuroprotective actions in preclinical models. In the current study, the safety of NeuroEPO was evaluated for the first time in humans.MethodsA phase I, randomized, parallel, open-label study was carried out in healthy volunteers. They received, intrana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 32 publications
3
25
1
Order By: Relevance
“…In human, a first evaluation on healthy human volunteers 27 indicated that 0.5 and 1 mg of Neuro‐EPO every 8 h during 4 days were well tolerated and had no erythropoiesis effect. More clinical trials at similar dosage are ongoing against stroke (acute treatment 1‐mg Neuro‐EPO by nasal route every 8 h for 3 days) and against long‐term neurodegenerative disease on mild–moderate Alzheimer patients and Parkinson patients 28,29 .…”
Section: Detection After a Single In Administrationmentioning
confidence: 99%
“…In human, a first evaluation on healthy human volunteers 27 indicated that 0.5 and 1 mg of Neuro‐EPO every 8 h during 4 days were well tolerated and had no erythropoiesis effect. More clinical trials at similar dosage are ongoing against stroke (acute treatment 1‐mg Neuro‐EPO by nasal route every 8 h for 3 days) and against long‐term neurodegenerative disease on mild–moderate Alzheimer patients and Parkinson patients 28,29 .…”
Section: Detection After a Single In Administrationmentioning
confidence: 99%
“…Further advances have been made also concerning administration route. Intranasal formulations of EPO and EPO-analogs have been developed in order to avoid repeated injections or high-dose systemic administration (Genc et al, 2011; Santos-Morales et al, 2017). Indeed, the nasal route can bypass the blood brain barrier with an optimal distribution in the cerebrospinal fluid and negligible flow in the systemic circulation, thus potentially hampering unwanted side effects (Genc et al, 2011).…”
Section: Erythropoietin As Therapeutic Compoundmentioning
confidence: 99%
“…There are already a few clinical studies exploring the intranasal route for a variety of inflammatory acute and chronic neurological conditions that require considerable systemic exposure . These studies are summarized in Table .…”
Section: Anti‐neuroinflammatory Treatment In Sepsismentioning
confidence: 99%